Biosynthesis of silver nanoparticles of Tribulus terrestris food supplement and evaluated antioxidant activity and collagenase, elastase and tyrosinase enzyme inhibition: In vitro and in silico approaches - Figueiredo, Célia Cristina Malaguti [UNESP]; da Costa Gomes, Amanda [UNESP]; Zibordi, Laura Camargo [UNESP]; Granero, Filipe Oliveira [UNESP]; Ximenes, Valdecir Farias [UNESP]; Pavan, Nathalia Mariana [UNESP]; Silva, Luciana Pereira; Sonvesso, Cibely da Silva Martin [UNESP]; Job, Aldo Eloizo [UNESP]; Nicolau-Junior, Nilson; Silva, Regildo Márcio Gonçalves da [UNESP] (Elsevier, 2023)
Food supplements from plants are source of many antioxidant substances. Tribulus terrestris food supplement (TtFS) is highlighted as one of these supplements that has presented potential to prevent damages and diseases caused by oxidative stress. In addition, new formulations that enhance the benefits of food supplement have been developed and metallic nanoparticles, the so-called green synthesis, has been of great interest. UV–visible spectroscopy, energy dispersive spectroscopy (EDS), Zeta potential (ZP), scanning transmission electron microscopy (STEM), scanning electron microscope (SEM) were used to characterize the synthesized silver nanoparticles (AgNPs). Antioxidant activity was determined by DPPH radical scavenging, ferric ion reducing power (FRAP); ABTS radical scavenging, and oxygen radical absorption capacity (ORAC-FL). Molecular docking analyses were performed to evaluate molecular interactions. Antioxidant evaluation of TtFS demonstrated 83.6% antioxidant activity (DPPH), 714.82 μM Trolox Equivalent (TE)/g sample (FRAP), 91.24 μM TE/g sample (ABTS), and antioxidant activity in ORAC assay. It presented inhibition activity on collagenase (75.33%), elastase (54.04%) and tyrosinase (59.07%). In addition, in silico assays showed an interaction between T. terrestris steroidal saponins and DNA, and the highest DNA binding affinity was observed with protodioscin. Steroidal saponins also presented interaction with all enzymes evaluated. The characterization of AgNPs demonstrated that they were formed as a spherical shape. These AgNPs showed greater protective properties against oxidative stress (85.41% antioxidant activity (DPPH) and 957.55 μM TE/g sample (FRAP)). The results represent an important indicator for the development and discovery of new nanoestructured pharmaceutical and cosmetic formulation using plants and natural products.
Keywords: Food supplements; Functional food; Molecular docking; Oxidative stress; Steroidal saponins